Effect Of Spraying Zinc On Growth And Production Of Two Cultivars Of Potato Plant Solanum tuberosum L. (NTU Journal of Agriculture and Veterinary Science, 2024)
A field experiment was conducted during the spring growing season of 2023 in Horticulture and Landscape Design / College of Agriculture and Forestry / University of Mosul to determine the effect of spraying zinc on growth and production of two cultivars of potato plant (Solanum tuberosum L.). Our experimentation consisted of two factors, the first one was two cultivars of imported potatoes (Elbeida and Laperla), the second included spraying plants with zinc at three concentrations (0, 500 and 750 mg.l-1), 6 treatments (2 x 3) included in this study and three replicates. The experimentation was carried out using a factorial experiment according to a Randomized complete block design (RCBD). The experiment results confirmed that Laperla cultivar significantly superior compared  to Elbeida cultivar in most of the studied traits, and spraying plants with 500 mg.l-1 of zinc recorded best values compared with 750 mg.l-1 of zinc.